Validation of Assessment for Learning Questionnaires for teachers and students. (6th December 2011) - Pat‐El, Ron Jonathan; Tillema, Harm; Segers, Mien; Vedder, Paul
Abstract : Background. Assessment can be a powerful force in promoting student learning. Still, few measures exist to gauge Assessment for Learning (AFL) in the classroom. Literature on AFL suggests that it encompasses both a monitor to track student progress as well as a scaffold to show or help students recognize in what areas they need to improve. Aims. Based on a review of recent attempts to measure the AFL, we constructed Assessment for Learning Questionnaires for Teachers (TAFL‐Q) and for students (SAFL‐Q) for evaluating perceptions regarding AFL practices in classrooms using matching items. Sample. The total sample included 1, 422 students (49% girls, 51% boys) and 237 teachers (43% females, 57% males) in lower vocational secondary education. Methods. The 28‐item questionnaires were examined by means of confirmatory factor analysis (CFA) using EQS on one random half of the sample. The CFA was cross‐validated on the second half. Measurement invariance tests were conducted to compare the students and teacher versions of the questionnaires. Results. CFA revealed a stable second‐order two‐factor structure that was cross‐validated: perceived monitoring, and perceived scaffolding subsumed under a common factor: AFL. Tests for measurement invariance showed that the parallel constructs were measured similarly for both students and teachers. Conclusion. The TAFL‐Q and SAFL‐Q capture the construct AFL in two subscales: Monitoring and Scaffolding, and allows for comparisons between teacher and student perceptions. The instruments can be useful tools for teachers and students alike to identify and scrutinize assessment practices in classroom.